Deafness and Sickle Cell Disease: Three Case Reports and Review of the Literature - Desai, Payal (J Clin Med Res, 2015)
The otological complications of sickle cell disease (SCD) in general and the audiological complications in particular are not well documented and studied. Because the general management of patients with SCD has improved after the advent of newborn screening, antibiotic prophylaxis, safer blood transfusion and hydroxyurea therapy, patients with SCD are doing better in general and living longer than before. With longer longevity, the incidence of new complications of SCD became apparent and previously milder complications became more severe and more common. The dental and otological complications of SCD are examples of these changes that have become more common than before. Unfortunately with this increase, there are no guidelines or recommendations based on evidence on how to manage and treat these complications. The aim of this study was to describe three patients with SCD and deafness due to three different causes that were not adequately treated and to review the literature of deafness in SCD. We hope this may initiate more controlled trials on the incidence, prevalence and management of these complications.